Comparing real driving emissions from Euro 6d-TEMP vehicles running on E0 and E10 gasoline blends - Shankar, V; Usan, I; Molden, N; Willman, C; Leach, FCP (SAE International, 2023)
Several governments are increasing the blending mandate of renewable fuels to reduce the life-cycle greenhouse gas emissions of the road transport sector. Currently, ethanol is a prominent renewable fuel and is used in low-level blends, such as E10 (10 %v/v ethanol, 90 %v/v gasoline) in many parts of the world. However, the exact concentration of ethanol amongst other renewable fuel components in commercially available fuels can vary and is not known.